2022
DOI: 10.1101/2022.11.06.515343
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Cousa objective: a long working distance air objective for multiphoton imagingin vivo

Abstract: Two-photon microscopy can resolve fluorescence dynamics deep in scattering tissue, but applying this technique in vivo is limited by short working distance water-immersion objectives. Here we present an ultra long working distance (20 mm) air objective called the Cousa objective. It is optimized for performance across multiphoton imaging wavelengths, offers a >4 mm^2 FOV with submicron lateral resolution, and is compatible with commonly used multiphoton imaging systems. We share the full optical prescriptio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…This will allow us to use a single preparation in which each mouse can be used to acquire data across multiple spatiotemporal scales during spontaneous and task-engaged behavioral epochs. Such combined recordings, with either Neuropixels or whole cell recording, may soon be possible with mesoscale 2p imaging, either on the Diesel 2p or the Thorlabs 2p mesoscope ( Sofroniew et al, 2016 ), by use of a recently developed air-immersion objective ( Yu et al, 2022 , bioRxiv). A similar mesoscale air-immersion 2p objective is also under development at Thorlabs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This will allow us to use a single preparation in which each mouse can be used to acquire data across multiple spatiotemporal scales during spontaneous and task-engaged behavioral epochs. Such combined recordings, with either Neuropixels or whole cell recording, may soon be possible with mesoscale 2p imaging, either on the Diesel 2p or the Thorlabs 2p mesoscope ( Sofroniew et al, 2016 ), by use of a recently developed air-immersion objective ( Yu et al, 2022 , bioRxiv). A similar mesoscale air-immersion 2p objective is also under development at Thorlabs.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in large-scale neural recording technology, such as widefield imaging ( Musall et al, 2019 ; Gallero-Salas et al, 2021 ; Esmaeili et al, 2021 ), large field-of-view (FOV) 2-photon (2p) imaging ( Sofroniew et al, 2016 ; Stringer et al, 2019 ; Yu et al, 2022 ), and Neuropixels high-density extracellular electrophysiology recordings ( Jun et al, 2017 ; Steinmetz et al, 2019 ) have allowed for rapid advancement in our understanding of the relationships between brain-wide neural activity and both spontaneous and task-engaged behavior in mice. For example, these techniques can now be deployed in recently developed behavioral paradigms that allow for the temporal separation of periods during which cortical activity is dominated by activity related to stimulus representation, choice/decision, maintenance of choice, and response or implementation of choice during different intra-trial epochs of 2-alternative forced choice (2-AFC) discrimination tasks ( Guo et al, 2014 ), the standardization of training and performance analysis across laboratories ( Aguillon-Rodriguez et al, 2021 ; eLife), and the separation of context-dependent rule representation and choice in a working memory task ( Wu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…x 0.5 𝑚𝑚 2 . Recent advancement in 3PM has shown vasculature imaging up to 716 𝜇m in the intact mouse brain with 2-mm FOV (Yu et al, 2024). However, 3PM requires low laser repetition rates for deep imaging to avoid thermal damage.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, high-resolution imaging is essential to minimize the risk of misattributing calcium transients ( Gauthier et al, 2022 ) in cellular calcium imaging. While large FOV two-photon microscopy (2PM) ( Sofroniew et al, 2016 ; Lu et al, 2020 ; Demas et al, 2021 ; Stirman et al, 2016 ; Yu et al, 2024 ; Clough et al, 2021 ; Ota et al, 2021 ; Rumyantsev et al, 2020 ; Tsai et al, 2015 ; Janiak et al, 2022 ) has demonstrated recording neural activities up to 5-mm FOV, the penetration depth of two-photon (2P) imaging is restricted to the shallow cortical layers in the intact mouse brain ( Wang and Xu, 2020 ; Wang et al, 2020 ; Takasaki et al, 2020 ). Moreover, achieving large FOV activity imaging often comes at the expense of reduced imaging resolution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation